PENGUKURAN TINGKAT EMISI RADIASI ELEKTROMAGNETIK KERETA REL LISTRIK TERHADAP LINGKUNGANNYA - Ardiatna, Wuwus; Mandaris, Dwi; Andiani, Dini; Arjadi, R. Harry (LIPI Press, 2010)
The amount of voltage that is used to run Electric Drive Train (Kereta Rel ListrikKRL) system simultaneously resulted on the electromagnetic fi eld radiation (EM). If the level of EM radiation exceeded the threshold of specifi ed standard, it will cause adverse effects to the environment. In this paper, measurements of EM radiation levels emitted by KRL (especially on Serpong-Tanah Abang) have been conducted. System and method of this measurement are based on the standard BS-EN 50121-2:2006. The results showed that the value of EM radiation levels generated by the KRL is below the threshold set by standard. The highest radiation levels occurred at frequency 936 MHz with fi eld strengths of 48.59 dB dB?V/m at horizontal antenna polarization.